Giving and sorting among friends: Evidence from a lab-in-the-field experiment - Christine Binzel; Dietmar Fehr (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
Among residents of an informal housing area in Cairo, we examine how dictator giving varies by the social distance between subjects - friend versus stranger - and by the anonymity of the dictator. While giving to strangers is high under anonymity, we find - consistent with Leider et al. (2009) - that (i) a decrease in social distance increases giving, (ii) giving to a stranger and to a friend is positively correlated, and (iii) more altruistic dictators increase their giving less under non-anonymity than less altruistic dictators. However, friends are not alike in their altruistic preferences, suggesting that an individual's intrinsic preferences may not necessarily be shaped by his (or her) peers. Instead, reciprocal motives seem important, indicating that social relationships may be valued differently when individuals are financially dependent on them.
Keywords: C93; D64; L14; O12; 330; giving; reciprocity; social distance; networks; sorting